Molecular identification and virulence of six isolates of Metarhizium anisopliae (Deuteromycotina: Hyphomycetes) to Bemisia tabaci Q biotype - Islam, Md. Touhidul; Omar , Dzolkhifli; Shabanimofrad, Mahmoodreza (Elsevier, 2014)
The aim of this study was to investigate the molecular identification and virulence of the entomopathogenic fungus Metarhizium anisopliae. Initially, the alignments of nucleotide sequences of the internal transcribed spacer (ITS) 1-5.8S-ITS4 regions of six isolates–TFFH1, TFFH3, PR1, MAP, GT3, and GT2–were investigated using GenBank ITS sequences for the same region and species of fungus. Thereafter, the in vitro (germination, vegetative growth, and sporulation) and the in vivo (%mortality of Bemisia tabaci) virulence of the fungus were investigated. A BLAST search of the ITS1 region revealed a match to a sequence registered under the accession number for M. anisopliae. The submitted sequence data were registered and provided with the accession numbers JX041507 to JX0415012, which were released in August 2012 (GenBank). In the virulence experiments, the highest germination percentage, vegetative growth, and sporulation of M. anisopliae were observed in the isolate PR1, with mean values of 97.2%, 4.6 cm, and 7.2 × 106 conidia/ml, respectively; while the highest mortality percentage of B. tabaci was observed in the isolate GT3, with an mean value of 84.3%. This study concludes that all the six tested isolates–TFFH1, TFFH3, PR1, MAP, GT3, and GT2–are M. anisopliae and the isolates PR1 and GT3 are more virulent to B. tabaci than that by the other four isolates.